Playing dead: mock trauma and folk drama in staged high school drunk-driving tragedies - Miller, Montana, author; Utah State University Press, publisher (Colorado State University. Libraries, 2012)
As the Grim Reaper pulls a student out of class to be a "victim" of drunk driving in a program called "Every 15 Minutes," Montana Miller observes the ritual through a folklorist's lens. Playing Dead examines why hundreds of American schools and communities each year organize these mock tragedies without any national sponsorship or coordination. Often, the event is complete with a staged accident in the parking lot, a life-flight helicopter, and faux eulogies for the "dead" students read in school assemblies.
Every 15 minutes someone dies -- Backdrop for the scene -- Marked for death: ambiguity and slippery steps in frames of play -- Engrossed out: every 15 minutes as folk drama -- The dazzle and darkness of play -- Shattering frames: the crash through YouTube's window -- Rustles in the gallery.
Keywords: Folklore -- Performance; Folk drama; High school students -- Psychology; Death -- Social aspects